Leukocyte esterase strip test as a reliable intraoperative PJIs biomarker. Our experience - Di Benedetto, Paolo; Dalla Vecchia, Giovanni; Dante, Federico; Gisonni, Renato; Cainero, Vanni; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2019)
ackgroud and aim of work: Prosthetic joint infection (PJI) is the most common cause of total knee replacement failure and the third most common cause of total hip replacement failure, accounting for 16.8% of all knee revisions and 14.8% of the hip revisions; nevertheless, the diagnosis of PJI is often a challenge for the orthopaedic surgeon. The aim of these study was to evaluate the reliability of the LE strip test for diagnosis of PJI. Materials and Methods: From December 2016 to January 2019, we enrolled 50 patients with suspected PJI; 32 females and 18 males, the average age at the time of the surgery was 76 years. Twenty-four patients underwent knee revision surgery and twenty-six hip revision surgery. In all patients during the surgery, the synovial fluid was aspirated and used for leukocyte esterase strip test. The result of the tests was compared to periprosthetic tissues culture, histological examination and sonication fluid culture for PJI. Results: Comparing the results obtained from the LE test with the results obtained from the other diagnostic methods, we found that the concordance between the results of the leukocyte-esterase test and those of the culture test with peri-prosthetic tissue or synovial fluid was shown to be 93%, between LE and histological examinations, the concordance was 93% and finally with the culture of the sonicated fluid the concordance was 86% of the cases. Conclusions: The results of our serie show a good intraoperative diagnostic accuracy of the LE test, especially in its ability to exclude the hypothesis of periprosthetic infection in case of a negative result.